Antiglutamate acid decarboxylase seropositive brain stem encephalitis. Issue 3 (10th March 2023) - AlAbdulghafoor, Faye; Behbehani, Raed; Johar, Abbas; Alroughani, Raed
Abstract : This is a case of a previously healthy female in her fourties presenting with a subacute presentation of bilateral horizontal gaze restriction, with bilateral lower motor facial palsy. The patient's daughter has type 1 diabetes. On investigation, the patient's MRI revealed a lesion in the dorsal medial pons. Cerebrospinal fluid analysis revealed albuminocytological dissociation, with a negative autoimmune panel. The patient was treated with intravenous immunoglobulin, and methylprednisolone for a total of 5 days and showed mild improvement. The patient had raised serum antiglutamic acid decarboxylase (anti-GAD) levels, and the final diagnosis of GAD seropositive brain stem encephalitis was made.